Iron status in healthy subjects living in Jordan - Qatatsheh, Ala Ali; Dabbour, Ibrahim R.; Al-rethaia, Abdallah S.; Al-Holy, Murad A.; Omar, Sharaf S. (Progress in Nutrition, 2016)
Summary. Iron status was determined in 240 subjects who referred for routine check up in Zarqa governorate hospital located in Jordan. Prevalence of ferritin deficiency (<16µg/l) was 3.4% (n=8) in males and 24.1% (n=58) in females of the studied population (P<0.05), while ferritin concentration >700µg/l was not observed. Prevalence of serum iron deficiency (<60 ng/mL) was 5.4% (n=13) in males and 18.8% (n=45) in females (P=0.01). Mean serum iron was 52.1±69.07 µg/l in females and 117.7±107.9 µg/l in males over 25 year old age (P=0.03). However, estimated mean serum concentration of ferritin was not affected by age and gender. These results revealed that Jordanian males eat higher dietary intake of iron than females, which is adequate to maintain adequate iron status with a low prevalence of iron deficiency.